2022
DOI: 10.7197/cmj.1149750
|View full text |Cite
|
Sign up to set email alerts
|

The healing effect of resveratrol and platelet rich plasma in corrosive esophagitis model in rats

Abstract: Background: Corrosive esophageal burns have high morbidity and mortality. The effective treatment is controversial. In our study, we aimed to examine the effects of resveratrol (RSV) and platelet rich plasma (PRP) on healing in the corrosive esophagitis model in rats. Material and methods: A total of 24 rats were randomly divided into 4 groups each as esophagitis, control, PRP and RSV groups. No treatment was administered to the control group. The esophagitis model was induced in the esophagitis and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Sun et al [55] studied xenograft tumors in the esophagus and found that gallic acid treatment reduced the volume of the esophageal carcinoma and Ki67 expression, a cell proliferation marker, via the Hippo signal pathway. Özden et al [56] investigated the roles of resveratrol in the corrosive esophagitis model and found that the total antioxidant status was increased, and the total oxidant status and levels of inflammation markers (IL1, IL6 and Tnfα) were decreased after resveratrol administration to rats. Another study showed that Carvacrol significantly restored the histopathology of CEB injury, induced re-epithelization, reduced apoptosis rate via downregulating the caspase-3 and reduced fibrosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [55] studied xenograft tumors in the esophagus and found that gallic acid treatment reduced the volume of the esophageal carcinoma and Ki67 expression, a cell proliferation marker, via the Hippo signal pathway. Özden et al [56] investigated the roles of resveratrol in the corrosive esophagitis model and found that the total antioxidant status was increased, and the total oxidant status and levels of inflammation markers (IL1, IL6 and Tnfα) were decreased after resveratrol administration to rats. Another study showed that Carvacrol significantly restored the histopathology of CEB injury, induced re-epithelization, reduced apoptosis rate via downregulating the caspase-3 and reduced fibrosis [36].…”
Section: Discussionmentioning
confidence: 99%